(untitled) (Tamaddun, 2017)
Indonesian language learning in schools is directed at improving students’ language skills, both in the aspects of listening, speaking, reading, and writing. Speaking is one of the language skills that is vulnerable in relation to spoken ethics. Language ethics is defined as a normative rule of language use which becomes a general guideline agreed by the language user community that such a method is recognized as a language that is polite, respectful, and in accordance with the values that apply in society. Someone who is skilled at speaking must consider what will be said before speaking. It is not wrong if the saying goes that language is someone’s personal mirror. The phrase shows that a person’s personality can be judged by his speech in language. For many people, good words, gentle, polite, will portray someone as a good person and virtuous character. Conversely, rude and bad words will also cause a bad image in the person. On that basis, Indonesian speech ethics has an important role in learning in schools which also contributes to the student’s character education curriculum.